Gothic iup, welsh uch, old irish uabar - Eric P. Hamp (Acta Neophilologica, 1992)
I wrote about Gothic iup ἄvω in relation to uf, ufar, German auf, Old English up, upp, etc., Latin sub, super, Umbrian sub, Oscan sup, Greek ὺπό and clearly related forms attested throughout Indo-European, in Modern Language Notes, January 1954, 39-41, without being able to reach a positive conclusion. All I could then establish was that the consonant was not the desired kind (apparently the nearly non-occurring IE *b), or else there was a strange unmotivated laryngeal suffix; that the initial required a laryngeal different from that which Albanian hyp ,mount, climb' leads us to assign to this base; and that iup could not be connected with uf.